A review focusing on the benefits of green tea catechins as nutraceuticals (Sciences of Phytochemistry, 2023)
Any product generated from food sources that offer additional health advantages over and above the essential nutritional content present in foods is referred to as a nutraceutical under the broad umbrella term. The catechins in Camellia sinensis (Theaceae) namely (-)-epicatechin, (-)-epicatechin-3-gallate, (-)-epigallocatechin, and (-)-epigallocatechin-3-gallate (EGCG), which can be used as nutraceuticals in food or as a component of food items has been discussed. Catechins being polyphenols and antioxidants are found to have a wide range of therapeutic application like weight loss, anticancer, anti-inflammatory, and a few more therapeutic applications, through various mechanisms like stimulating AMP-activated protein kinase, enhanced apoptosis, decreased expression of interleukin (IL)-6 and IL-8. The most recent method for extracting catechins include combining the extraction processing of PEF or IPL with Subcritical water extraction. Food additives have been mixed with green tea extracts to develop a desired formulation like chewing gum and capsule. As green tea catechins are a beneficial phytoconstituents to improve overall health, its prospects include formulation of a gelatin gummy formulation which will improve its palatability by masking the bitter taste. Gelatin gummy formulation can be carried conveniently and will provide easy access to the consumer as compared to green tea. Furthermore, we found a scope to develop an analytical method for EGCG and carry out its validation by HPLC which will be more reliable and cost-efficient in comparison to the existing UHPLC methods for EGCG.